The Inception of Ideas: How Students Use ChatGPT for Academic Writing - Dewi, Finita (Fakultas Seni Rupa dan Desain ITB, 2024)
This study investigated the experiences of students who have used ChatGPT for writing assistance. A survey was conducted to collect data on students' usage frequency, preferences, and perceptions of ChatGPT's suggestions for improving their writing. The survey also explored if students encountered any technical issues while using ChatGPT and whether they found it helpful in overcoming writer's block or not. Results showed students preferred ChatGPT over other writing tools and found its suggestions helpful and accurate. Most students felt that ChatGPT was equally helpful across different types of writing. Although some technical issues were reported, they were relatively minor. Overall, students reported increased confidence in their writing abilities after using ChatGPT and would recommend it to other students. Incorporating ChatGPT into the writing process may help students overcome writer's block and improve their writing habits. This study suggests that ChatGPT is a useful tool for students who require writing assistance, and its suggestions are perceived as helpful and accurate.